The genus Eremiothrips (Thysanoptera: Thripidae) in Iran, with one new species - Minaei, Kambiz (Zootaxa, 2012)
Eremiothrips bhattii sp.n. is described from Fars province, Iran. Three other species of this genus that have previously beenrecorded from other parts of Iran, E. similis Bhatti, E. taghizadehi (zur Strassen) and E. varius (Bhatti) are reported from Fars province for the first time. A key is provided for identification of the Iranian Eremiothrips species based on males.